Determinants of oral health-related quality of life of the institutionalized elderly - Zenthöfer, Andreas; Rammelsberg, Peter; Schröder, Johannes; Hassel, Alexander J. (Psychogeriatrics, 2014)
Background Diminished oral health of the institutionalized elderly has frequently been reported. This is not only of significance with regard to nutrition and general health, but it can also affect oral health-related quality of life. This paper evaluates the effects of oral and general conditions on oral health-related quality of life for the institutionalized elderly, as measured by the Geriatric Oral Health Assessment Index (GOHAI). Materials and Methods Ninety-four residents of four long-term care homes in southern Germany agreed to participate in this study, and interviews were conducted using the GOHAI questionnaire. The Revised Oral Health Assessment Guide was applied to allocate participants into two groups: satisfactory oral health and poor oral health. To evaluate the effects of age, gender, number of chronic diseases, frequently taken drugs, care level, Mini-Mental State Examination score, periodontitis (for participants with their own teeth), pressures caused by prostheses, and type of denture worn, a linear regression model with the total GOHAI score was calculated with these determinants. Results The mean ± SD GOHAI score was 53.3 ± 6.2 in the satisfactory oral health group and 48.7 ± 7.3 in the poor oral health group. Statistical analysis showed that the GOHAI scores were significantly different in satisfactory oral health and poor oral health groups (P = 0.030) and were affected by care level (P = 0.008) and type of dentures worn (P = 0.006). Conclusions Within the limitations of this study, it can be concluded that oral health-related quality of life of the institutionalized elderly is low and is positively associated with better oral health.